2021
DOI: 10.1111/cogs.12957
|View full text |Cite
|
Sign up to set email alerts
|

Action Generalization Across Group Members: Action Efficiency Matters

Abstract: Actions are usually generalized among social group members. Importantly, the efficiency of an action with respect to achieving an external target determines action understanding, and it may have different degrees of social relevance to social groups. Thus, this study explored the role of action efficiency in action generalization. We used computer animations to simulate actions in social groups initiated by visual action cues or category labels, and we measured differences in response times between identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Social groups specify boundaries for individuals and can activate categorical thinking (Bodenhausen et al, 2012; Rhodes & Baron, 2019). It has been documented that when making predictions about unknown members of social groups, people tend to generalize the actions of known members to them, showing person-to-person generalization (Duan et al, 2021; Powell & Spelke, 2013; Xu et al, 2019; Yin et al, 2022). Such action generalization was found to be held very early in development (Powell & Spelke, 2013) and, importantly, was not observed when social group cues were removed (Xu et al, 2019).…”
Section: Beliefs Of Shared Goals About Social Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…Social groups specify boundaries for individuals and can activate categorical thinking (Bodenhausen et al, 2012; Rhodes & Baron, 2019). It has been documented that when making predictions about unknown members of social groups, people tend to generalize the actions of known members to them, showing person-to-person generalization (Duan et al, 2021; Powell & Spelke, 2013; Xu et al, 2019; Yin et al, 2022). Such action generalization was found to be held very early in development (Powell & Spelke, 2013) and, importantly, was not observed when social group cues were removed (Xu et al, 2019).…”
Section: Beliefs Of Shared Goals About Social Groupsmentioning
confidence: 99%
“…How are these two types of action properties generalized? Duan et al (2021) reported that when the observed group members perform the same inefficient movements toward an external goal, the movements are more likely to be generalized to other group members, as these inefficient movements may come to represent relevant norms and rituals shared by a social group (Kapitány & Nielsen, 2015; Legare & Souza, 2012). Moreover, when both movements and goals are available, action generalization is based on common goals, instead of shallow-level movements, among group members (Yin et al, 2022).…”
Section: Beliefs Of Shared Goals About Social Groupsmentioning
confidence: 99%
See 3 more Smart Citations